In search of meaningful feedback conversations. Issue 3 (14th February 2018) - LaDonna, Kori A; Watling, Christopher
Abstract : LaDonna and Watling argue for the value of embracing vulnerability and inspiring honest conversation to enhance the meaningfulness of feedback